Acid-base state of the preterm infant and the formulation of intravenous feeding solutions. Issue 4 (April 1990) - MacMahon, P; Mayne, P D; Blair, M; Pope, C; Kovar, I Z
Abstract : An acidic intravenous source of phosphorus (Addiphos) was compared with dipotassium hydrogen phosphate in 25 preterm infants to study acid-base state. Eight infants were given either Addiphos or dipotassium hydrogen phosphate alternately for 48 hour periods and similar amounts of calcium and phosphorus were delivered. There were no significant differences in calcium and phosphorus intake, calcium and phosphate plasma concentrations, or acid-base state between study periods on the two solutions. Seventeen infants were given the two solutions alternately for 72 hour periods; Addiphos was used to increase the amounts of calcium and phosphorus being delivered. Calcium and phosphorus intake was decreased on dipotassium hydrogen phosphate, but Addiphos significantly increased calcium and phosphorus intake and plasma calcium and phosphate concentrations. It also lowered the pH of the urine and raised the titratable acidity. Acid-base state, however, was not significantly different. It is therefore possible to increase intake of calcium and phosphorus in preterm infants without causing a significant metabolic acidosis.